Strategy and mechanisms for implementing the digital economy in the EU and Ukraine as a condition for overcoming the crisis (Economics and region, 2023)
The purpose of the article is to study the strategies and mechanisms of the introduction of the digital economy in the EU countries and Ukraine as a condition for overcoming crisis phenomena. As a result of the analysis and generalization of the works of domestic and foreign scientists, it was determined that the “digital economy” is a branch of the economy that uses digital technologies, the Internet and other information technologies to create, distribute and process information for the purpose of creating value. It is noted that the essence of the digital economy of the EU countries and Ukraine is that digital technologies allow collecting, storing, processing and analyzing large volumes of data in a short time. This allows the business to quickly respond to changing market conditions, and also ensures more efficient use of resources. As a result of the research, the components of the digital economy of the EU countries and Ukraine were considered: digital literacy, finance and platforms, digital technologies and infrastructure, e-government and e-services, e-commerce, digital media and internet marketing, cyber security, data and analytics. The mechanisms for implementing the digital economy in European countries that are leaders in the field of innovation and technology, actively develop digital technologies and infrastructure, create new innovative products and services, have developed electronic government systems, which contribute to increasing the efficiency of public administration and increasing the level of citizens’ trust in authorities. The peculiarities of the development of the digital economy of Ukraine are considered. The main prospects for further scientific research in this area are the determination of strategic directions for the development and implementation of digital economy mechanisms in Ukraine to overcome crisis phenomena in the economy. The development of the digital economy in Ukraine is an important direction of the country’s development, which provides opportunities for creating new business models, increasing competitiveness, and supporting economic growth.
Keywords: international movement of technologies; digital economy; e-commerce; digitalization; cyber security; informatization